Islamic Banking : How Has it Diffused? - Imam, Patrick (IMF Working Papers; Working Paper ;, 2010)
This paper investigates the determinants of the pattern of Islamic bank diffusion around the world using country-level data for 1992 - 2006. The analysis illustrates that income per capita, share of Muslims in the population and status as an oil producer are linked to the development of Islamic banking, as are economic integration with Middle Eastern countries and proximity to Islamic financial centers. Interest rates have a negative impact on Islamic banking, reflecting the implicit benchmark for Islamic banks. The quality of institutions does not matter, probably because the often higher hurdle set by Shariah law trumps the quality of local institutions in most countries. The 9/11 attacks were not important to the diffusion of Islamic banking; but they coincided with rising oil prices, which are a significant factor in the diffusion of Islamic banking. Islamic banks also appear to be complements to, rather than substitutes for, conventional banks.